Relationships Between Family Support and Self-Care To The Quality Of Life Of Patients With Type 2 Diabetes Mellitus at Puskesmas Kabaena Barat, Bombana, 2020 - Dewi Ulfani; Safruddin Safruddin; Sudarman Sudarman (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Diabetes Mellitus (DM) is a substantial problem for global. So far, more research revealed about the clinical problem of DM. The purpose of this study was to determine the factors affecting the quality of life of type 2 DM patients at the Puskesmas Kabaena Barat. Quantitative types, with a cross-sectional research design. purposive sampling technique with 35 respondents. Research shows that there is a relationship between depression with quality of life of patients with type 2 Diabetes Mellitus (p = 0.001), there was no relationship between family support and quality of life for type 2 diabetes mellitus patients (p = 0.109), there is a relationship between self-care with the quality of life of type 2 DM patients (p = 0.004). This study concludes the fewer individual perceptions of the quality of life of Type 2 DM patients.